Modeling and Simulation of UPFC or Dynamic Voltage Control in Power System Using PSCAD/EMTDC Software - S. N., Fadilah; N., Md. Saad; M. F., Abas; Noor Lina, Ramli (2015)
This paper discussed the effect of Unified Power Flow Controller (UPFC) controllers for enhancement of power system voltage regulation and power flows in the transmission system. The model of UPFC are studied and validated in power system computer aided design & electromagnetic transient direct current (PSCAD/EMTDC) environment. The basic operations are explained, as well as the control strategies and circuit configurations of the controller. PI controller is used for control scheme. In this proposed work, the 4 bus test system is used to verify the proposed model. The steady-state analysis is done to show the capability of the controller in improving voltage regulation in the transmission system.